Diagnostic outcomes for molecular genetic testing in children with suspected Ehlers–Danlos syndrome. Issue 5 (6th February 2022) - Damseh, Nadirah; Dupuis, Lucie; O'Connor, Constance; Oh, Rachel Youjin; Wang, Yi Wen; Stavropoulos, Dimitri James; Schwartz, Sarah B.; Mendoza‐Londono, Roberto
Abstract: Ehlers–Danlos syndrome (EDS) is a heterogeneous group of connective tissue disorders characterized by hyperextensible skin, hypermobile joints, easy bruisability, and fragility of the connective tissues. The diagnosis is based on clinical assessment and phenotype‐guided genetic testing. Most EDS subtypes can be confirmed by genetic testing except for hypermobile EDS. This study explored the utility of applying the 2017 EDS classification criteria and molecular genetic testing in establishing an EDS diagnosis in children. In this retrospective study, we reviewed 72 patients referred to a tertiary care center for evaluation of EDS who underwent one or more forms of genetic testing. Eighteen patients (18/72, 25%) met the clinical criteria for one of the EDS subtypes and of these, 15 (15/18, 83%) were confirmed molecularly. Fifty‐four patients (54/72, 75%) had features that overlapped EDS and other syndromes associated with joint hypermobility but did not fully meet clinical criteria. Twelve of them (12/54, 22%) were later shown to have a positive molecular genetic diagnosis of EDS. Different molecular genetic tests were performed on the cohort of 72 patients (EDS panel, n = 44; microarray, n = 25; whole exome sequencing [WES], n = 9; single gene sequencing, n = 3; familial variant testing, n = 10; other genetic panels n = 3). EDS panel was completed in 44 patients (61%), and a molecular diagnosis was confirmed in nine of the patients who satisfied criteria for one of the EDS subtypes (9/12, 75%) and in nine of the patients who did not fully meet criteria (9/32, 28%). We observed a correlation between generalized joint hypermobility, poor healing, easy bruising, atrophic scars, skin hyperextensibility, and developmental dysplasia of the hip with a positive molecular result. This study provides guidance for the use of molecular genetic testing in combination with the 2017 clinical diagnostic criteria in children presenting with EDS characteristics.